Comfort zones : planning your future - Chapman, Elwood N. (Crisp Pub. Menlo ParkUS, 1997)
Covers the retirement planning basics. Helps the reader to develop personal strategies for making the transition from work to retirement; and having retired, for managing health, relationships, finances etc. Appendices deal with retirement activities; job-getting skills; and planning for retirement.